2022
DOI: 10.3390/polym14235287
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Severely Deformed Polypropylene in ECAE (Equal Channel Angular Extrusion) via Routes A and C

Abstract: Equal channel angular extrusion (ECAE) is a solid-state extrusion process for modifying microstructures via severe plastic deformation without modifying the specimen cross section. In this study, changes in the microstructure and mechanical properties of polypropylene resulting from extrusion orientation route A (no rotation between extrusions) and extrusion orientation route C (a rotation of 180° between extrusions) are investigated using a 90° die-angle tooling outfitted with back pressure. Important differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…30) The possibility of forming biaxially oriented structures in the strain range e = 6.78.5, consisting of larger and more perfect crystallites connected by a large number of stretched tie chains, the possibility of activating phase transformations (occurrence of crystal polymorphism and the formation of crystalline phases with higher plasticity or thermal stability), makes it possible to obtain a unique combination of multiple increased values of stiffness, strength (with low anisotropy of the latter) and wear resistance, while maintaining plasticity at a level close to that of the original samples. 27,30,46) Compared to the latter, the density and melting point increase. Figure 3 shows an example of the dependence of tensile strength and strain at break on accumulated strain for high density polyethylene subjected to ECMAE.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…30) The possibility of forming biaxially oriented structures in the strain range e = 6.78.5, consisting of larger and more perfect crystallites connected by a large number of stretched tie chains, the possibility of activating phase transformations (occurrence of crystal polymorphism and the formation of crystalline phases with higher plasticity or thermal stability), makes it possible to obtain a unique combination of multiple increased values of stiffness, strength (with low anisotropy of the latter) and wear resistance, while maintaining plasticity at a level close to that of the original samples. 27,30,46) Compared to the latter, the density and melting point increase. Figure 3 shows an example of the dependence of tensile strength and strain at break on accumulated strain for high density polyethylene subjected to ECMAE.…”
mentioning
confidence: 96%
“…Textural changes also occurred in this region of accumulated strain, but the crystalline textures differed from each other depending on their localization in the sample volume, as there was a deformation gradient in the transverse direction and the local plastic strain decreased from the top to the bottom of the sample. 20,27) At the same time, there was a steady flow region where the plastic strain was quite uniform along the longitudinal direction except for the edges. It was observed that routes A and C reached their saturation levels quickly (after about four passes, e = 3.3), compared to routes B A and B C , which require a high number of passes to reach their steady state.…”
mentioning
confidence: 97%
See 1 more Smart Citation